Purinergic Signaling in the Vertebrate Olfactory System - Rotermund, Natalie; Schulz, Kristina; Hirnet, Daniela; Lohr, Christian (Frontiers in Cellular Neuroscience, 2019)
Adenosine 5'-triphosphate (ATP) is an ubiquitous co-transmitter in the vertebrate brain. ATP itself, as well as its breakdown products ADP and adenosine are involved in synaptic transmission and plasticity, neuron-glia communication and neural development. Although purinoceptors have been demonstrated in the vertebrate olfactory system by means of histological techniques for many years, detailed insights into physiological properties and functional significance of purinergic signaling in olfaction have been published only recently. We review the current literature on purinergic neuromodulation, neuron-glia interactions and neurogenesis in the vertebrate olfactory system.